Prenatal particulate air pollution exposure and expression of the miR-17/92 cluster in cord blood: Findings from the ENVIRONAGE birth cohort - Tsamou, Maria; Nawrot, Tim S.; Carollo, Riccardo M.; Trippas, Ann-Julie; Lefebvre, Wouter; Vanpoucke, Charlotte; Vrijens, Karen (Environment international, 2020)
•MiR-17, miR-20a and miR-92a were inversely associated with prenatal PM2.5 exposure.•Cluster activator C-MYC was inversely associated prenatal PM2.5 exposure.•No association between the cluster target CDKN1A and gestational PM2.5 exposure. Air pollution exposure during pregnancy is an important environmental health issue. Epigenetics mediate the effects of prenatal exposure and could increase disease predisposition in later life. The oncogenic miR-17/92 cluster is involved in normal development and disease. Here, for the first time the potential prenatal effects of particulate matter with a diameter<2.5 μm (PM2.5) exposure on expression of the miR-17/92 cluster in cord blood are explored. In 370 mother-newborn pairs from the ENVIRONAGE birth cohort, expression of three members of the miR-17/92 cluster was measured in cord blood by qRT-PCR. Expression of C-MYC and CDKN1A, a cluster activator and a target gene, respectively, was also analyzed. Multivariable linear regression models were used to associate the relative m(i)RNA expression with prenatal PM2.5 exposure. PM2.5 exposure averaged (10th-90th percentile) 11.7 (9.0–14.4) µg/m3 over the entire pregnancy. In cord blood, miR-17 and miR-20a showed a −45.0% (95%CI: −55.9 to −31.4, p < 0.0001) and a –33.7% (95%CI: −46.9 to −17.2, p = 0.0003), decrease in expression in association with first trimester PM2.5 exposure, and a –32.5% (95%CI: −45.6 to −16.3, p = 0.0004) and –23.3% (95%CI: −38.1 to −4.8, p = 0.02), respectively, decrease in expression in association with PM2.5 exposure during the entire pregnancy. In association with third trimester PM2.5 exposure, a reduction of −25.8% (95%CI: −40.2 to −8.0, p = 0.007) and −14.2% (95%CI: −27.7 to 1.9, p = 0.08), for miR-20a and miR-92a expression, respectively, was identified. Only miR-92a expression (-15.7%, 95%CI: −27.3 to −2.4, p = 0.02) was associated with PM2.5 exposure during the last month of pregnancy. C-MYC expression was downregulated in cord blood in association with prenatal PM2.5 exposure during the first trimester and the entire pregnancy, in the adjusted model. Lower expression levels of the miR-17/92 cluster in cord blood in association with increased prenatal PM2.5 exposure were observed. Whether this oncogenic microRNA cluster plays a role in trans-placental carcinogenesis remains to be elucidated.